Test case generation for semantic-based user input validation of web applications. (2018) - Hanna, Samer; Munro, Malcolm
Semantic-based user input validation of web applications is important because of the central role these applications play in our daily lives. An example of such a process is in rejecting a four-digit number as an input that represents the age of a web application user. Testing professionals must write test cases that can be used to check if a web application can handle semantically invalid inputs. Most of the current approaches for test case generation for web applications do not consider the semantics of inputs. And for approaches that do consider input semantics, test case generation is done manually. This paper defines a process that can be used to automate and in some cases, semi-automate the generation of test cases to assess semantic-based user input validation of web applications (TCSUIV). To prove the usefulness of the process in this paper, it is applied to case study web page. A prototype tool has been built also to show the applicability of this paper process for test case generation for web application.